The Study of Antibacterial Effect of The Extraction of Linum Usitatissimum an Some Pathogenic Bacteria - M.M. Abdullah; M. T. Al-Kaisey; H. A. R. Al- Awad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The present investigation aims to evaluate the antibacterial activity of hexane , methanol , ethanol and chloroform extracts of Al- Maha linseed culivar against some pathogenic miroorganism. including gram- positive (Bacillus subtilis and Staphylococcus aureus( gram - negative (Escherichia coli and Pseudomonas). The oil (hexane extract) showed significant inhibition activity compared to the other extracts against the tested microorganisms . The oil extract showed pronounced activity even in lowers (up to 0.5%) concentration against all tested microorganisms.Meanwhile. the gram - positive bacteria was found more sensitive than those of the gram -negative bacteria. The inhibition actions of the absolute ethanol extract of the seeds against the tested microorganisms were variable from ne species to the others Therefore, Staph aureus were more sensitive (the inhibition ratio was 92%) followed by P. aercginosa (91%), B. subtilis (89%). E, coli (84%). The absolute methanol and choroform extracts of the linseed gave the Same inhibition actions against the tested microorganisms . The higher sensitivity was observed on the P. aeroginose followed by Staph. aureus. E. coli and B. subilis,